English Rhythm: Better than Imitation - Bello, Carlos; Cerón, Arturo; Ramírez, José (CIEX JOURNAL, 2018)
A language can be better learned by their sounds, such as the recognition of a song we like when we hear it just for a few seconds. Allowing English learners to recognize these sounds with funny and dynamics exercises will be the tool for teachers to develop in their students oral skills by doing the development consciously.